HMG‐CoA reductase inhibition medicated hypocholesterolemic and antiatherosclerotic potential of phytoconstituents of an aqueous pod extract of Prosopis cineraria (L.) Druce: In silico, in vitro, and in vivo studies - Noopur Jaipal; Heera Ram; Jaykaran Charan; Anshuman Dixit; Garima Singh; Bhim P. Singh; Ashok Kumar; Anil Panwar (eFood, 2022)
Abstract Hydrophilic bioactive compounds are copiously exhibited in aqueous extracts owed to solubility. The study was assigned to assess the ability of phytoconstituents of aqueous pod extract of Prosopis cineraria to inhibit 3‐hydroxy‐3‐methylglutary‐coenzyme A (HMG‐CoA) reductase activity and regression in atherosclerotic plaque through in vitro, in vivo, and in silico assessments along with phytochemistry of extract. The test extract exhibited 17 leading compounds as examined by Liquid Chromatograph Triple Quadrupole Mass Spectroscope. In vitro assay of test extract showed 78.1% inhibition of HMG‐CoA inhibition (IC50 was 0.03 μg/ml). In vivo assessments, hypercholesterolemia was induced by supplementing cholesterol powder and a high‐fat diet. The treatment of test extract caused significant (p ≤ 0.001) improvements in the lipid profile and antioxidant levels. Subsequently, the reductions in the atherosclerotic plaque and improved lumen volume were pointedly observed. In silico analyses of molecular docking revealed potent interaction capabilities of cloprostenol with the target protein of HMGR. The interactions were validated through structural simulations of the molecular dynamics such as root mean square fluctuation, the radius of gyration, and solvent accessible surface area. The druggability of potent compounds was also examined. The results revealed that phytoconstituents of the test extract could inhibit HMGR and regress atherosclerotic plaque.